The relations between dynamic capabilities and core competencies on the case of Polish companies - Paweł Cegliński (Administrative Sciences, 2020)
This article deals with the relationship between dynamic capabilities and core competencies of companies. Both categories extend the resource-based view of the firm. They are difficult to work out, but thanks to their durability and universality they enable to achieve a sustainable competitive advantage. Due to intensive changes in the business environment and increasing difficulty in forecasting them, the importance of adaptability based on both categories increases. The presented results of the research of two leading Polish companies-Panek S.A. and Cukiernia Sowa-are practical examples of the impact of dynamic capabilities on the creation of core competencies and indirectly core and end products and services. The analysis is the basis for improvement of future research.
Keywords: 350; case study; core competencies; dynamic capabilities; strategic management